Institutions, Criminal Violence and Interdependence: The Narrow Path of Development in Latin America and the Caribbean - Rogelio Madrueño (Íconos)
The objective of this article is to examine the complexities of economic and social change from a global perspective with a focus on Latin American and the Caribbean. The academic literature in this area has emphasized the importance of institutional change as a central factor underlying economic growth over the long term. However the thrust behind this literature has not fully incorporated the relevance of interdependence from a dynamic perspective. Interdependence emphasizes the integral nature of social, economic and institutional transformation over the short, medium and long terms. This article attempts to shed light on central aspects and factors of surrounding crime and development from a multi-dimensional perspective in which the relationship between criminal violence, institutions and interdependence are key factors. An analytical framework is presented in conjunction with an empirical analysis on the impacts of criminal delinquency and criminal violence on the dynamics of economic growth per capita of the global economy, underlining the case of the Latin American and Caribbean region between 1990-2010.